(untitled) (Biocenosis, 2025)
Costa Rica hosts more than 4% of the world’s biodiversity; however, several fauna groups are highly threatened. The Parque Ambiental Municipal Río Tiribí (PAMRT – Municipal Tiribi River Environmental Park), located in the canton of La Union, Cartago, represents a space with great potential for biodiversity research, conservation and education. The study aimed to document the participatory biological monitoring experience carried out in the PAMRT, focusing on recording fauna species present in the area. For this purpose, four participatory bird counts were conducted in April, June, September and December 2024, covering approximately 4 km of trails within the park and recording observations using the eBird application. Herpetofauna monitoring was carried out through monthly participatory night walks along rivers and streams between May and November 2024, using the intensive search method, and the records were documented in the Epicollect5 application. As a result, seven bird species were identified as being threatened to some degree, as well as seven endemic species to Costa Rica and Panama. In addition, seven amphibian species and three reptile species were recorded, including the endangered Isthmohyla rivularis. In conclusion, citizen participation is a key component in biodiversity research and monitoring in urban spaces and protected areas and it contributes significantly to the development of conservation strategies.